(untitled) (International Journal of Engineering and Computer Science, 2017)
As the countries become industrialized, the pollution level to our environments increases and this pollution becomes a major problem for the health of the population and also affects the ecosystem. Although some standards are set with environmental authorities for wastes emissions in air, the monitoring and controlling of that standards are still a challenge in most industries especially chemical industries and cement factories. To avoid such adverse imbalances in the nature, an air pollution monitoring system is utmost important. Some of the pollution monitoring systems in cement factories are OPSIS, Uras26, Magnos27 and CODEL. These systems are installed to monitor the emissions from chimney only. Wireless Sensor Networks is an excellent technology that can sense, measure, and gather information from the real world and based on some local decision process it transmit the sensed data to the user. These networks allow the physical environment to be measured at any point, and greatly increase the quality of the environment. This paper reviews the importance of employing wireless sensor networks in air pollution monitoring in cement factories along with their advantages and disadvantages